DISRUPTIONS AMONG DIGITAL NATIVES IN TERTIARY LEVEL CLASSROOMS - Kristina a/p Francis, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Students today grow up with technology in hand. They are identified as digital natives or net generation as they are grown up with digital technology and the internet. In the current era, students from most countries which are developed are using digital technologies and the internet for their learning in tertiary level classrooms. This typically refers to those who had grown up since the mid to late 1990’s, when the Internet became accessible to a wide population (Herman, 2017). Millennial and Generation Z populations are also included in the usage of digital technologies. Digital devices help students to stay connected and communicate around the world. Although these devices are an advantage to students yet, some are being too dependent especially in their tertiary level classrooms and thus, these digital devices become disruptive. When digital devices become disruptive, it contributes to serious alarming issues among students especially in hindering the learning process in tertiary level classrooms. These are the challenges faced by most educators in tertiary level classrooms. Therefore, to curb these challenges, it is vital for educators to identify and learn the digital habits of students before developing strategies for overcoming these issues. It is vital to find out the causes of disruptions in the learning process in tertiary level classrooms. This research was conducted among undergraduate students in UTAR. The findings concluded that most of the students use their digital devices for various purposes. Among the purposes, it is mainly found that unnecessarily, students are using their digital devices in the tertiary level classrooms without specific purposes and especially uses their devices which do not relate to the teaching and learning process in tertiary level classrooms. Thus, this leads to students being disruptive in the classrooms and eventually impact on students’ academic excellence as well as the university’s overall academic achievement. Through the findings from this study, it is important for educators in the tertiary classrooms to implement effectual steps in the future to limit students from using their digital devices for unnecessary purposes in the tertiary level classrooms.